UPAYA GO-JEK DALAM MENINGKATKAN EKSPANSI BISNIS INTERNASIONAL DI VIETNAM TAHUN 2018-2022 - Utari, Febrianti; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Go-Jek is an Indonesian-born start-up company that has expanded to several countries in Southeast Asia. Go-Jek entered Vietnam by investing in go-viet, expanding with the local brand "GoViet", starting expansion to Vietnam in 2018 and experiencing successes and challenges. GoViet is well received in Vietnamese markets, especially in big cities. By 2020, GoVet will be rebranding to Go-Jek, strengthening its identity and integration with the GoJek ecosystem, as well as offering efficient services through more advanced technology. This research uses a qualitative method with a case study approach used to collect and analyze data from secondary sources. Secondary data is obtained from various secondary resources such as books, documents, newspapers, journals, and websites on all data about the Go-Jek expansion in Vietnam. The theory used in this study is Foreign Direct Investment theory, with a liberal perspective and using a group level of analysis. The results of the research showed that Go-Jek in its expansion to Vietnam faced strict competition from other players such as Grab, had to navigate complex local regulations and policies, as well as adapting services to local cultural preferences and needs in Vietnam. However, with its strategy and efforts, it succeeded in becoming one of the leading players in the Vietnamese market despite facing significant challenges, demonstrating strong adaptability and competitiveness in the international market. Keywords: International Business, Foreign Direct Investments, Multinational Corporations.